Escape Short Narratives in Galician and Portuguese Literature: Comparative Study of the imagery and common space in Cinco Dias, Cinco Noites and Amigo medo - Colom Jiménez, María (Madrygal. Revista de Estudios Gallegos, 2020)
Fleeing, exile and migration from one country to another for political reasons and cross-border journeys have been object of literary representation. This study aims to analyse, from a comparative point of view, the short narratives Cinco Dias, Cinco Noites (1975), by Manuel Tiago, and Amigo medo (2002), by Xavier López Rodríguez, as short fleeing narratives, inserted within denunciation narratives. The study focuses on the construction of a galician-portuguese space and the imagery in these novels, as well as, relating to the literary elements used in the novels which exemplify the themes of escape narratives from the last half of the 20th Century.